THE MAIN TASKS AND DIRECTIONS OF MILITARY PATRIOTISM EDUCATION OF STUDENTS, WAYS TO ACHIEVE EFFICIENCY IN MILITARY PATRIOTISM EDUCATION - Khasanov Nurmukhammad Khaydarali ugli, (International Journal of Innovations in Engineering Research and Technology, 2023)
In this article, the successful solution to the issues of strengthening the defense of our country is closely related to youth education, political consciousness, labor activity, and the speed of scientific and technical development. Education consists of objectively based processes of directing people to physical and mental work or other useful activities for society, and at the same time preparing them to perform multifaceted social tasks. Information is given that military patriotism education is considered an integral part of it.